Cultivating meaningful work for early-career professionals - Nelesh Dhanpat; Lerato Mabeso; Masego Madiba; Kabelo Malete; Lindiwe Mashanye (SA Journal of Industrial Psychology, 2025)
Orientation: The concept of meaningful work has gained considerable attention in research, yet limited focus exists on early-career professionals’ workplace experiences.